2018
DOI: 10.5194/isprs-annals-iv-2-97-2018
|View full text |Cite
|
Sign up to set email alerts
|

A Voxel-Based Metadata Structure for Change Detection in Point Clouds of Large-Scale Urban Areas

Abstract: ABSTRACT:Mobile laser scanning has not only the potential to create detailed representations of urban environments, but also to determine changes up to a very detailed level. An environment representation for change detection in large scale urban environments based on point clouds has drawbacks in terms of memory scalability. Volumes, however, are a promising building block for memory efficient change detection methods. The challenge of working with 3D occupancy grids is that the usual raycasting-based methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Based on the theoretical foundation of this work, Gehrung et al (2016) proposed a concept for occupancy representation on a global scale. In addition, an algorithm for iterative refinement has been proposed in order to reduce discretization artifacts inherent to the technology as well as to speed up the generation of the occupancy octree (Gehrung et al, 2018).…”
Section: Occupancy Gridsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the theoretical foundation of this work, Gehrung et al (2016) proposed a concept for occupancy representation on a global scale. In addition, an algorithm for iterative refinement has been proposed in order to reduce discretization artifacts inherent to the technology as well as to speed up the generation of the occupancy octree (Gehrung et al, 2018).…”
Section: Occupancy Gridsmentioning
confidence: 99%
“…Following a well established practice regarding evidence grids used in works such as the one of Hornung et al (2013), octree cells are considered to be independent of each other. The octree is generated using iterative refinement, such as presented by Gehrung et al (2018), since it is less resource intensive than normal ray casting.…”
Section: Representationmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the theoretical foundation of this work, we proposed a concept for occupancy representation on a global scale (Gehrung et al, 2016). Later on, an algorithm for iterative refinement has been proposed that also prevents artifacts caused by discretization inherent to occupancy grids (Gehrung et al, 2018). It was also shown that the probabilistic occupancy grids can be used to extract moving objects (Gehrung et al, 2017).…”
Section: Occupancy Gridsmentioning
confidence: 99%
“…With regard to the hardware, we based the design of the vehicle on past experiences with the development of an airborne laser scanning system (Schatz, 2008). Currently we use the vehicle for several research topics in the area of object detection and tracking (Becker et al, 2016;Borgmann et al, 2017Borgmann et al, , 2018Hammer et al, 2018), mobile mapping and change detection (Gehrung et al, 2018). In the later part of this paper, we present the use case of pedestrian detection, which uses several capabilities of the vehicle.…”
Section: Introductionmentioning
confidence: 99%